Differential regulation of calcium-NFAT signaling pathway by Akt isoforms: unraveling effector dynamics and exhaustion of cytotoxic T lymphocytes in tumor microenvironment - Hung-Chih Yang; Li-Rung Huang; Ulrike Protzer; Wen-Ling Chen; Yong-Lin Chang; Su-Fang Lin; Masanori Isogawa (Journal for ImmunoTherapy of Cancer)
Background Impairment of Akt signaling has been observed in antigen-specific cytotoxic T lymphocytes (CTLs) during chronic viral infections or tumor progression. Despite numerous studies emphasizing Akt’s role in driving CTL effector functions, there is limited exploration of using Akt molecules in T-cell engineering to enhance their antiviral or antitumor capabilities for therapeutic purposes. Some studies even conclude that inhibiting Akt activation during the in vitro expansion process can prevent T-cell exhaustion and boost the antitumor effector functions of chimeric antigen receptor-T cells in vivo. Given the unique expression patterns and functions of the three Akt isoforms in immune cells, we proposed that Akt isoforms in CTLs may regulate effector functions and T-cell exhaustion distinctly.Methods In this study, we genetically modified tumor/virus-antigen-specific T-cell receptor tg CTLs to ectopically express Akt isoforms via retroviral transduction. We subsequently conducted western blotting, flow cytometry, and RNA sequencing analysis to assess their Akt expression, expression of immune checkpoints, antitumor/antivirus functionalities, and transcriptome. Additionally, we employed a persistent Hepatitis B Virus mouse model and a syngeneic hepatocellular carcinoma mouse model for further evaluation of their antivirus/antitumor efficacies.Results We found that both Akt1 and Akt2 overexpression enhanced the cytotoxic capabilities of mouse CTLs, although with different dynamics. Specifically, Akt2 signaling in CTLs accelerated effector functions, leading to a rapid attack on tumor cells. Conversely, Akt1 signaling triggered calcium influx and subsequent nuclear factor of activated T cells (NFAT) activation, while Akt2 signaling suppressed calcium influx, preventing excessive NFAT expression and nuclear translocation. This repression of NFAT transcriptional activity by Akt2 signaling during prolonged antigen stimulation subsequently led to reduced expression of transcription factors associated with T-cell exhaustion, such as Egr2, Nr4a, Tox, and immune checkpoints. Consequently, Akt2-overexpressed CTLs displayed reduced T-cell exhaustion within the tumor microenvironment and efficiently eradicated tumors.Conclusion These findings highlight the essential role of Akt signaling in enabling tumor-specific CTLs to eliminate cancer cells in the solid TME, with Akt isoforms differentially regulating the calcium–calcineurin–NFAT signaling pathway. This discovery suggests the potential of AKT2 in T-cell engineering technology to enhance the survival and effector functions of adoptively transferred T cells for treating liver malignancies or chronic viral infections.